2002
DOI: 10.1159/000063331
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Adenosine on Antegrade Fast Pathway, Antegrade Slow Pathway, and Retrograde Fast Pathway in Atrioventricular Nodal Reentry

Abstract: Adenosine has a potent negative dromotropic effect. However, comparative effects of adenosine on the three pathways of atrioventricular (AV) nodal reentry remain unclear. In this study, we sought to determine the effects of adenosine on the antegrade fast, antegrade slow, and retrograde fast pathway conduction in patients with AV nodal reentrant tachycardia (AVNRT). Twenty patients with common slow-fast AVNRT (mean cycle length 360 ± 49 ms) were studied. The effects of adenosine on the antegrade slow pathway a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…25 39 40 Adenosine is effective in terminating AV nodal re-entry tachycardias, but these have also been reported as having been induced by adenosine 41 ; indeed Curtis et al found that low dose adenosine could induce AV nodal re-entrant tachycardias in 9 of 16 patients who were known to experience this tachycardia. The effect of adenosine on the underlying dual AV node pathways in these patients was investigated, and in common with other workers, 42 adenosine was shown preferentially to block the fast antegrade pathway, thus allowing a re-entry circuit to develop. A similar response to adenosine has been observed when it was erroneously given to a patient with a sinus tachycardia (personal communication), who had presented to the emergency department with a history of recurrent palpitation; on three consecutive occasions a brief period of narrow complex tachycardia (probably AV nodal re-entry tachycardia) was induced, followed by return to sinus tachycardia.…”
Section: Reports Of Tachyarrhythmiasmentioning
confidence: 67%
“…25 39 40 Adenosine is effective in terminating AV nodal re-entry tachycardias, but these have also been reported as having been induced by adenosine 41 ; indeed Curtis et al found that low dose adenosine could induce AV nodal re-entrant tachycardias in 9 of 16 patients who were known to experience this tachycardia. The effect of adenosine on the underlying dual AV node pathways in these patients was investigated, and in common with other workers, 42 adenosine was shown preferentially to block the fast antegrade pathway, thus allowing a re-entry circuit to develop. A similar response to adenosine has been observed when it was erroneously given to a patient with a sinus tachycardia (personal communication), who had presented to the emergency department with a history of recurrent palpitation; on three consecutive occasions a brief period of narrow complex tachycardia (probably AV nodal re-entry tachycardia) was induced, followed by return to sinus tachycardia.…”
Section: Reports Of Tachyarrhythmiasmentioning
confidence: 67%
“…24 Current literature notes that antegrade FP exhibits heightened sensitivity to ATP relative to antegrade SP. 25 In this specific case, ATP selectively inhibited antegrade FP, allowing the remaining antegrade SP to become more pronounced. We propose that ATP injection during atrial pacing could serve as a potential diagnostic tool for both DAVNNT and AVNRT patients.…”
Section: Discussionmentioning
confidence: 89%
“…However, this alternative scenario is unlikely, since the anterograde slow AV nodal pathway is notably more sensitive to adenosine than the retrograde fast AV nodal pathway. 6 , 7 , 8 Therefore, in response to adenosine, NV-dependent ART would be expected to terminate in the anterograde limb (slow AV nodal pathway), not the retrograde limb. Accordingly, because of persistence of conduction over the slow AV nodal and NV pathways following termination of tachycardia, and because of the presence of fusion beats during tachycardia, we deduce that the tachycardia had an intra-Mahaim pathway origin and that termination of tachycardia with adenosine was due solely to its direct effects on the Mahaim pathway.…”
Section: Case Reportmentioning
confidence: 99%